2006
DOI: 10.1111/j.1540-8191.2006.00268.x
|View full text |Cite
|
Sign up to set email alerts
|

In Which Patients Should Sheathless IABP be Used? An Analysis of Vascular Complications in 1211 Cases

Abstract: PAD, DM, and sheathed insertion technique are the major risk factors of ischemia during IABP use. Among all these risk factors, the only modifiable risk factor is the use of introducer sheath. With the presence of PAD and DM, the choice of sheathed method would increase the probability of ischemia almost 35 times. Sheathless method of insertion should be preferred in patients with DM and PAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 11 publications
1
33
0
4
Order By: Relevance
“…Severe peripheral vascular disease represents the most important risk factor for vascular complications which, in turn, constitute the largest proportion of all IABP-related complications [16,[18][19][20][21][22].…”
Section: Contraindicationsmentioning
confidence: 99%
“…Severe peripheral vascular disease represents the most important risk factor for vascular complications which, in turn, constitute the largest proportion of all IABP-related complications [16,[18][19][20][21][22].…”
Section: Contraindicationsmentioning
confidence: 99%
“…Ważnym czynnikiem ryzyka tego powikłania jest LEAD, a wstępne zastentowanie tętnicy biodrowej z użyciem urządzenia bezkoszulkowego może pozwolić na uniknięcie takich powikłań [420]. Te powikła-nia są również częste u pacjentów leczonych urządzeniami do wspomagania czynności lewej komory, których koszulki naczyniowe są zwykle większe, co powoduje zwiększenie śmiertelności 30-dniowej u osób z LEAD [421].…”
Section: Choroby Tętnic Obwodowychunclassified
“…4,5 Sheaths can allow easy placement of the catheter and reduce the risk of haemorrhage at the site of arterial entrance. However, the use of a sheath can decrease the luminal surface of the IABP for distal blood flow and lead to a slow flow area that can result in thrombus production 6 -an effect which could be lessened when a sheathless catheter is used. Erdogan et al 6 has previously reported that the cross-sectional area of the IABP without sheath is 7.87 mm 2 whereas it is 11.53 mm 2 with sheath usage, corresponding to a 31.7% increase in the cross-sectional area of the IABP with a sheath.…”
Section: Introductionmentioning
confidence: 98%
“…However, the use of a sheath can decrease the luminal surface of the IABP for distal blood flow and lead to a slow flow area that can result in thrombus production 6 -an effect which could be lessened when a sheathless catheter is used. Erdogan et al 6 has previously reported that the cross-sectional area of the IABP without sheath is 7.87 mm 2 whereas it is 11.53 mm 2 with sheath usage, corresponding to a 31.7% increase in the cross-sectional area of the IABP with a sheath. This increase in the cross-sectional area, as expected, can be associated with a decrease in distal blood flow and consequently an increase in the risk of thrombus formation in the extremities.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation